ANALYSIS OF ONLINE MODELS IN THE INDEPENDENT CAMPUS - Mulyanto, Agus Iwan (Perspektif : Jurnal Ilmu Administrasi, 2020)
Rapid response When the Minister of Education and Culture issued Circular Letter No. 3 of 2020 concerning the Prevention of Covid-19 must be taken to take effective prevention and mitigation measures for the outbreak that has now become a global pandemic. This article analyzes the implementation of online learning in the era of independent learning and independent campus under COVID-19 conditions. With library research methods that refer to resources available online, this article presents a perspective of service activist learning about strategies to deal with conditions that are difficult to predict. From the results of theoretical analysis, there is no uniformity of understanding of information about the characteristics of the plague in the government as a regulator, discussing the understanding of the main definitions related to the problem of online learning with the perspective of independent learning and independent campuses. The choice that most allows lecturers in 'free teaching' so that they focus more on efforts to transfer knowledge and skills to students. The policy can also encourage students to be more innovative and creative in learning (student-centered learning) is online. The physical encounter will not be abandoned even though advances in virtual and digital technology have thickened. Although the COVID-19 outbreak will last a long time, there is no harm in having to think about patterns and methods of physical and social learning that are safe for everyone. The development of communication and digital technology has a significant role that can be utilized as widely as possible by academia to look brighter future.